Engineering Spin-Wave Dynamics in Magnetic Nanowires: The Role of Morphology and Aspect Ratio - Escrig-Murua, J; Saavedra-Díaz, E (American Institute of Physics, 2025)
Magnetic nanowires are key components in spintronic and high-frequency applications due to their tunable magnetization dynamics and spin-wave properties. In this work, we investigate the influence of nanowire morphology on their dynamic susceptibility and resonant modes using micromagnetic simulations. We analyze cylindrical, capped cylindrical, and ellipsoidal nanowires across a range of aspect ratios to determine how structural variations affect spin-wave excitation and localization. Our results reveal that cylindrical and capped cylindrical nanowires exhibit multiple resonant peaks, corresponding to edge and bulk spin-wave modes, with higher-order bulk modes emerging at larger aspect ratios. In contrast, ellipsoidal nanowires primarily support a single dominant resonance mode, suggesting a suppression of bulk modes due to a more uniform magnetization distribution. The demagnetizing field analysis confirms that this suppression arises from a stronger field concentration at the extremities in ellipsoidal nanowires. Additionally, energy minimization calculations show that ellipsoidal nanowires exhibit more metastable states, highlighting the role of termination geometry in stabilizing different magnetization configurations. These findings provide insights into the design of magnetic nanowires for future technological applications, particularly in magnonic circuits, non-reciprocal microwave components, and next-generation signal processing devices. © 2025 Author(s).